The Model of Learning and Teaching on Midwifery Course for Nursing Students to Prepare for Register Nurse Licensing Examination - เครือแก้ว, จัณทร์ปภัสร์; กฤษเจริญ, สุรีย์พร; พลอินทร์, กัญจนี; ชัชเวช, วรางคณา; แก้วพิมล, ปรียา (Princess of Naradhiwas University Journal, 2018)
This descriptive qualitative research aimed at investigating the learning and teaching process of Midwifery and Midwifery Practice subjects, and revision of Midwifery knowledge for the licensing examination and registration for Professionalism of Nursing. The samples were 28 nursing graduates in the academic year 2015 at the Faculty of Nursing, Prince of Songkla University. The data were collected from July until September 2015 by group discussion and in-depth interviews. Also, content analysis methods was applied to this study. The results revealed that there are three parts of the models of learning and teaching process and preparing the students for the nursing licensing examination and registration for Professionalism of Nursing. First, in the theory part, the model of teaching including the experience of self-learning and instructional media responding to the students are attractive. Second, the practicum part invloves actual experience presenting in class, motivation from instructors at clinical teaching, and appropriate areas of learning. Finally, the reviewing of knowledge part contains self-preparing and the strategy of reviewing by lecturers. Based on the above of outcomes, applicable development of learning and teaching of Midwifery can be presented to relevant institutions in order to help nursing students to achieve as registered Nursing and Obstetric License tests.